WAVE PROPAGATION THROUGH HOLLOW BODIES AND NOISE REDUCTION - GERMÈS, SYLVAIN; STAWICKI, CHRISTOPHE; AUBRY, DENIS (Journal of computational acoustics, 2001)
Low frequency noise (2–200 Hz) reduction in the passenger compartment has emerged in the past few years as a crucial subject of research in the car industry. This kind of noise is mainly due to the panels' vibrations, therefore our aim is to decrease the part of structural energy that reach them, i.e., we want to increase the part of energy that dissipates while propagating in the car body frame. This approach requires the understanding of structural wave propagation through the beam like structure (pillar, cross members…) as well as reflection and transmission at the structural joints. This is the physical problem that we want to address in this paper. Since car body frames are much too complex for physical understanding, we focused on simpler representative academic structures. We developed a numerical tool for the prediction and visualization of wave propagation, based on finite element models (FEM). Our FEM are first validated by comparison with experimental modal analysis, and then used for transient analysis. In both cases, the good agreement between calculations and experiments shows the reliability of our model and allows us to use it for wave propagation visualization. We illustrate our results by making a movie that helps to understand how waves propagate through a two hollow bodies junction.